Policy implementation in mid-western Uganda: Examining personnel resources, financial capacity, administrative capability and political support - Mwesigwa, David (Goodwood Publishing, 2022)
Purpose: This study aimed to examine the level of personnel resources, financial capacity, administrative capability and political support in Hoima district local government in mid-western Uganda. Research Methodology: A descriptive survey of 194 respondents comprising of elected local councillors and technical officials were randomly selected from Hoima district. Four issues were investigated, namely personnel resources, financial capacity, administrative capability and political support. SPSS (version 15) was used for data analysis. A total of 164 respondents took part in the study. Results: Policy implementation at local governments in Uganda was moderate; this was manifested in terms of personnel resources, financial capacity, administrative capability and political support, which, if each of them can be improved, the degree of policy implementation will improve. Financial and non-financial factors both need to be improved for achieving a preferred level of policy implementation at local governments. Limitations: This study zeroed on policy implementation alone and yet a number of issues affecting policy implementation may not necessarily originate from it but from policy formulation, which was never covered. Contribution: This study highlights the four aspects in policy implementation, viz. personnel resources, financial resources, administrative capability, and political support; these are very significant to policy managers at grass root government. Hoima district is encouraged to consider all four aspects for effective policy implementation.